TINJAUAN YURIDIS TERHADAP PENGATURAN PENGUASAAN DAN PENGGUNAAN TANAH PADA KAWASAN SEMPADAN SUNGAI DI KECAMATAN DAMAI KABUPATEN KUTAI BARAT - Sariyah Sariyah (Journal of Law ( Jurnal Ilmu Hukum ), 2015)
BSTRACTION       In life of everyday us, where us Do activity, aktifitas, effort etcetera, all begining from land;ground, and earth which we tread on is ground land, source of everything come. Because groundland is something that of vital importance, hence government make a order in Constitution 1945, section 33, and in making furthermore other rule in code Number 5 Year 1960 about regulation of specifics of agraria        Law Number 5 Year 1960, section 6 sound: All Land Right Have Social Pungsi. Hence with existence of ground land owning social pungsi of government make a order to be can in adhering to do well by legal body, individual or group of people, etcetera. Social function related to ground land is white colars development, university and schoolhouse, hospital, final place of exile ( TPA), place funeral of public ( TPU), market, plantation location and agriculture, town garden, conducting garden, river border and other covert area.      With existence of regulation of local government of Sub-Province of Kutai West, hence division of regional zona according to allotment can be executed according to rule of regulation of perundang-unddangan. For example: Area protected forest, protected forest area and energy kindness, area development of town and kampong, plantation area and agriculture.Keyword: Usage of Land;Ground at river border area, pursuant to perda of Year no.32 2005 bar sub-province.